The Smoothing Hypothesis: An Alternative Test. - Barefield, Russell M.; Comiskey, Eugene E. (The Accounting Review, 1972)
This article presents information on the smoothing hypothesis in accounting. This hypothesis assumes that managers perceive their performance measure to be a decreasing function of earnings variability. Based upon this assumption, managers could be expected to make accounting policy decisions which tend to smooth reported earnings. The focus of this paper is on the differential impact of the cost versus the equity method of accounting for unconsolidated subsidiaries. Assuming that dividends typically fluctuate less than earnings, one might reason that the cost method would generally result in smoother reported earnings for the parent. However, closer examination shows that even if subsidiary dividends fluctuate less than subsidiary earnings, the equity basis can still result in smoother reported earnings. The least squares criterion was used to develop a linear relationship between earnings and time on each basis. The slope co-efficient of the line was used as an estimate of the rate of growth in before-tax earnings. Thus, each firm had a growth rate estimate for each valuation basis. The variability of earnings about the linear trend line described above provided the basis for a measurement of earnings variability. The actual measure of earnings variability used was the mean square error (MSE) of earnings about the linear trend line standardized by dividing by average earnings over the time period considered.